The Relationship Between Moral Foundations and Emotions - Melike Yaşar; Serap Akgün (Psikoloji Çalışmaları)
Moral foundations theory posits six moral foundations that guide moral judgment, namely, care, fairness, loyalty, authority, sanctity, and liberty. The theory states that the violation of fairness promotes anger, while doing so for sanctity elicits feelings of disgust. Meanwhile, violation of care is associated with anger toward the perpetrator and compassion for the victim. Only a few empirical studies test the propositions of the theory on the relationship between the violation of moral foundation and emotions, which were conducted in western culture. The current study investigates the relationships between moral transgressions and emotions in a nonwestern culture. It also examined feelings toward perpetrators and victims in the face of moral violation. In the pilot study conducted to determine the relevant scenarios to be used in the research, 187 participants evaluated whether or not the behaviors described in 52 scenarios were morally wrong and to report their feelings in these situations. The main study analyzed the participants’ moral judgment, feelings toward moral violations, emotional reaction toward victims and perpetrators, and decisions on the punishment of perpetrators using the 12 moral violation scenarios identified in the pilot study. Toward this end, data were collected from 72 participants. To test whether the emotion experienced during the violation of one moral foundation is higher than that experienced in the violation of another, the study conducted a 2(gender) × 6(moral foundations) factorial multivariate analysis of variance (MANOVA) of moral foundations that involved repeated measures. The result indicated that violations of the foundations of justice and care were morally viewed as more wrong than those of other foundations. However, the findings pointed out that emotions guide moral judgment, and feelings toward victims and perpetrators differ accorrding to the violated moral foundations.